Inovasi Pengelolaan Pembelajaran Bahasa Jepang Di SMA Lab School Universitas Pendidikan Indonesia (UPI) Bandung - Falang Kencana Kartiwa; Nur Sasongko , Rambat (Manajer Pendididikan, 2023)
at SMA Lab School Universitas Pendidikan Indonesia (UPI) conducted by Japanese language teachers. This study used a qualitative approach with the research subjects including the principal, head of curriculum, Japanese language teachers, and students at SMA Lab School UPI. The data collection techniques used include observation, interview, and documentation study. The results showed that innovation in the management of Japanese language learning by Japanese language teachers at UPI Lab School High School is in accordance with the curriculum implemented by UPI Lab School High School. Specific findings include: (1). Successful planning, with effective planning steps and in accordance with the needs of Japanese language learning. (2). Good organization, where the Japanese language learning organization system has been well structured and facilitates the smooth learning process. (3). Good implementation, with Japanese teachers able to implement effective learning methods and strategies in the classroom. (4). Continuous evaluation, where Japanese teachers regularly evaluate students' progress and learning outcomes to ensure teaching effectiveness. (5). Finding some problems in Japanese learning innovation at UPI Lab School High School that need to be addressed and improved in order to increase learning effectiveness. Thus, this study provides an overview of innovations in the management of Japanese language learning at UPI Lab School High School and highlights some aspects that need to be considered in order to improve the quality of Japanese language learning at the school.